2018
DOI: 10.1155/2018/4742574
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status and Its Associated Risk Factors among Adults in the Southwest Region of Cameroon

Abstract: Background Vitamin D has been shown to exert its actions on the musculoskeletal, gastrointestinal, prostate, renal, endocrine, immune, and cardiovascular systems. Current reported data of hypovitaminosis D reveals a global pandemic, with an estimated one billion people worldwide presenting with hypovitaminosis D. Objective This study aimed at investigating the vitamin D status and its associated risk factors in Cameroonians from the South West Region. Method The study was a community- and hospital-based prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…The high prevalence of vitamin D deficiency found in our work is similar to that reported by Arnedo-Pena (45.1%) [13]. In the general population, the prevalence of vitamin D deficiency is lower; in the study of Tangoh et al [14] in Cameroon, and was 3.2%. In USA, Pasquale M. et al has reported a high prevalence of hypovitaminosis D among HIV-infected subjects ranging from 70.3 to 83.7% [15].…”
Section: Discussionsupporting
confidence: 89%
“…The high prevalence of vitamin D deficiency found in our work is similar to that reported by Arnedo-Pena (45.1%) [13]. In the general population, the prevalence of vitamin D deficiency is lower; in the study of Tangoh et al [14] in Cameroon, and was 3.2%. In USA, Pasquale M. et al has reported a high prevalence of hypovitaminosis D among HIV-infected subjects ranging from 70.3 to 83.7% [15].…”
Section: Discussionsupporting
confidence: 89%
“…5,12) Furthermore, a clinical study reported a significant negative correlation between vitamin D levels and fatty degeneration of rotator cuff muscles and a positive correlation between serum vitamin D and shoulder isokinetic muscle torque. 11) Several studies have reported risk factors of hypovitaminosis D. 1,2,4,[13][14][15][16] Age, degree of sun exposure, race, and/or body mass index (BMI) have all been reported to affect the prevalence of hypovitaminosis D. 1,2,13,14) Little exposure to sunlight is a known risk factor of hypovitaminosis D, but the effect of age has not been firmly established. Furthermore, these known risk factors of hypovitaminosis D have not been thoroughly investigated in patients with a rotator cuff tear.…”
mentioning
confidence: 99%
“…[ 29 ] The urban residents had the highest levels of 25(OH)D, followed by rural residents and the lowest for large metro residents in the American population in a study done by Bailey et al [ 31 ] The community in which the participants belonged did not have any significant influence on the vitamin D level, according to Tangoh et al , indicating that the level of urbanization may not affect vitamin D status. [ 32 ] 25(OH)D levels were indifferent across different levels of educational qualification and income status in the current study. Subjects with a higher level of education had lower 25(OH)D levels in a study done by Al Zarooni et al [ 29 ] There was no significant difference in vitamin D levels between levels of education and income levels in another study by Tangoh et al [ 32 ]…”
Section: Discussionmentioning
confidence: 50%
“…[ 32 ] 25(OH)D levels were indifferent across different levels of educational qualification and income status in the current study. Subjects with a higher level of education had lower 25(OH)D levels in a study done by Al Zarooni et al [ 29 ] There was no significant difference in vitamin D levels between levels of education and income levels in another study by Tangoh et al [ 32 ]…”
Section: Discussionmentioning
confidence: 65%